2009
DOI: 10.1007/s12039-009-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic investigation of lanthanum-substituted strontium-oxybritholites

Abstract: Lanthanum-substituted strontium-oxybritholites, Sr 10-x La x (PO 4 ) 6-x (SiO 4 ) x O with x = 0, 2 and 4, prepared by solid state reaction were investigated by chemical analysis, powder X-ray diffraction, Raman and 29 Si MAS NMR spectroscopies. The refinements of powder XRD patterns of the substituted compounds by the Rietveld method showed that the lanthanum occupied the two metal sites, i.e. (4f) and (6h) sites into the apatite structure, with a clear preference for the (6h) sites. A progressive shift of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The explanation of the effect of substitution on the a-axis is not as obvious because of the different sizes of the substituted ions. The comparison of the obtained parameter values with those determined by K. Boughzala for the same compounds, prepared at high temperature [37],…”
Section: Lattice Parametersmentioning
confidence: 78%
“…The explanation of the effect of substitution on the a-axis is not as obvious because of the different sizes of the substituted ions. The comparison of the obtained parameter values with those determined by K. Boughzala for the same compounds, prepared at high temperature [37],…”
Section: Lattice Parametersmentioning
confidence: 78%
“…The mixed‐valent europium(II,III) oxide phosphate is structurally related to Eu II 5 (PO 4 ) 3 X ( X = F, Cl, OH), Ca II 10 (PO 4 ) 6 O, and Sr II 10 (PO 4 ) 6 O [ a = 9.750(4) Å, c = 7.278(3) Å] . Its lattice parameters are slightly smaller than those of strontium(II) oxide phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Along the zone axis 0 0 l no intensity outside the Bragg reflections due to structure modulation was observed, pointing to a rather random disorder. We assume a similar disorder as in Sr II 10 (PO 4 ) 6 O but with a higher occupancy for the corresponding oxygen atom to compensate the additional charge per formula unit due to the incorporation of Eu 3+ at the expense of Eu 2+ [according to Eu II 10– x Eu III x (PO 4 ) 6 O 1+ x /2 ]. Despite this uncertainty, the simulation of the XRPD pattern (Figure ) based on the structure model from SXRD matches the observed pattern nicely.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have analyzed the occupancy of lanthanide ions between the two crystallographic sites in the apatitic structure. Several works indicate that the La atoms are distributed between the two crystallographic sites M(1) and M(2) in apatite structure, with a clear preference for the larger site M(2), demonstrating that the nature of the channel anion plays a significant role in the distribution of La 3+ between the two cationic sites [25,26]. Furthermore, Ardhaoui et al [27,28] indicated that the introduction of La 3+ in the apatite structure has a strong influence on its stability.…”
Section: X-ray Analysismentioning
confidence: 99%